The Development of Experimental Sets for Measuring Linear Thermal Expansion Coefficient of Metal Using Digital Video-Based Single Slit Diffraction Method - Yuri Yogaswara; Fourier Dzar Eljabbar Latief (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2018)
The development of an apparatus for the measurement of linear thermal expansion coefficient of metal by a single diffraction method has been developed. The development was made based on several ideas from previous researchers, as well as to overcome several limitations which yields insignificant results. The development includes the redesign of the primary holder module, the temperature measurement module (using a thermocouple sensor connected to the PC), and the measurement approach of the diffraction pattern distance by means of digital video analysis techniques using Tracker software. The development of the modules as well as the measurement approach that has been done yields very good experimental results. The measured linear thermal expansion coefficient of aluminum has a high level of accuracy and precision. The result is (23.100 ± 0.2186)×10-6/°C, and compared from a reference, i.e., 23.000 × 10-6/°C, the relative error of is 0.95% and the relative standard deviation is 0.43%.